2022
DOI: 10.1111/cla.12510
|View full text |Cite
|
Sign up to set email alerts
|

Female terminalia morphology and cladistic relations among Tok‐Tok beetles (Tenebrionidae: Sepidiini)

Abstract: Tok-tokkies are one of the most iconic lineages within Tenebrionidae. In addition to containing some of the largest darkling beetles, this tribe is recognized for its remarkable form of sexual communication known as substrate tapping. Nevertheless, the phylogenetic relationships within the group remain poorly understood. This study investigates the usefulness of female terminalia morphology for delimiting Sepidiini and reconstructing relationships among it. Data on the structure of the ovipositors, genital tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…That clade also includes Sepidiini and Adelostomini, which do not occur in South America ( Bouchard et al, 2021 ). Kamiński et al (2022) suggested Sepidiini and Adelostomini as closely related tribes, considering the morphology of female terminalia and several genes. However, they did not place Elenophorini close to these tribes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That clade also includes Sepidiini and Adelostomini, which do not occur in South America ( Bouchard et al, 2021 ). Kamiński et al (2022) suggested Sepidiini and Adelostomini as closely related tribes, considering the morphology of female terminalia and several genes. However, they did not place Elenophorini close to these tribes.…”
Section: Discussionmentioning
confidence: 99%
“…Blapstinus appears to be the only tenebrionid genus from the Atacama Desert that has close relatives in North America. The corresponding subtribe Blapstinina Mulsant & Rey, 1853 is in fact restricted to Nearctic and Neotropical regions ( Lumen et al, 2020 ; Kamiński et al, 2022 ). Monophyly of the analyzed taxa of Lagriinae, Blaptinae, Stenochinae, and Alleculinae was confirmed with maximum branch supports, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, within the tribe, the genus displays some degree of morphological similarity toward representatives of Blapstinina Mulsant and Rey, 1853 (Lumen et al . 2019, Kamiński et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Both genera are clearly distinguished by the different structures of antennae (stenolamoid sensoria in Stenolamus vs simple sensoria in Dilamus ), and temporae (postocular sulcus on tempora in Stenolamus vs rounded tempora in Dilamus ). The first of these features seems to be exclusively assigned to Stenolamus within the whole Blaptinae, which all lack compound sensoria (Kamiński et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological terminology follows that of Matthews at al. (2010), with additional specialized terms used for the female terminalia following Kamiński et al (2022) . Dissections were performed following methodology illustrated by Kamiński (2021) ; specimens were soaked in 10% KOH solution for dissection of genitalia before staining with chlorazol black.…”
Section: Materials and Methodsmentioning
confidence: 99%